Legal Mechanism of Implementing the Concept of Circular Economy in the Post-Soviet Space (in Terms of Russia) - Anisimov, Aleksey Pavlovich; Ryzhenkov, Anatoliy Jakovlevich (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
The article deals with the main provisions of the concept of circular economy in the context of political, educational, legal and other transformations without which achievement of the set goals is impossible. The authors pay special attention to analysis of the legal mechanism of achieving the goals and objectives in the area of reducing the volume of waste produced in the country, creating conditions for development of technologies for its treatment and reuse. This requires formation of the new legal category of â€œenvironmental entrepreneurshipâ€, along with establishment of the system of incentives, permissions, restrictions and prohibitions aimed at a radical change of the existing model of waste management in legal acts of the system. Development of this legal institution will lead to adjustment of a number of civil agreements, including further development of environmental insurance and environmental audit agreements.